Evaluation of effectiveness of methods for effective spectrum width information and the biggest weight of the pitch tone in the tasks of identification and authentication of audio signals - Юдін, О.К.; Зюбіна, Р.В. (Science-based technologies, 2017)
It is determined that identification by voice contributes to the reliability of the use of protection systems critical information. The analysis of existing methods of determining the fundamental tone frequency that you selected the most convenient method for the determination of the fundamental frequency, namely the method of spectral harmonic analysis. An evaluation of the effectiveness of the developed methods effective spectral width and the largest scales the information of the fundamental tone in the tasks of identification of audio signals. As a result of the experiment for three groups of speech signals, was determined that the method for effective spectrum width allows to identify the speaker with a probability of 100%, where a value SNR of 4.27 dB for extensibility identification and of 5.29 dB for textualizing in conditions, when the input signal belongs to one of the subsets of the database; if the input signal belongs to a database, not divided into subsets, the value of SNR 5.22 dB is amount of 5.26 dB, respectively.